2017
DOI: 10.1016/j.xphs.2017.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Polysorbate 20 and Polysorbate 80 on the Higher-Order Structure of a Monoclonal Antibody and Its Fab and Fc Fragments Probed Using 2D Nuclear Magnetic Resonance Spectroscopy

Abstract: We examined how polysorbate 20 (PS20; Tween 20) and polysorbate 80 (PS80; Tween 80) affect the higher order structure of a monoclonal antibody (mAb) and its Fab and Fc fragments, using near-UV circular dichroism and 2D NMR. Both polysorbates bind to the mAb with sub-millimolar affinity. Binding causes significant changes in the tertiary structure of mAb with no changes in its secondary structure. 2D 13C-1H methyl NMR indicates that with increasing concentration of polysorbates, the Fab region showed a decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(54 citation statements)
references
References 70 publications
2
52
0
Order By: Relevance
“…Under carefully controlled conditions, and given suitably low residual moisture content (<0.5%), lyophilization is known to be capable of increasing storage stability. 73 Based on the above considerations, the observed thermal stability differences between the native state of bevacizumab and all other samples studied may be represented by one or both of the following sample dependent variables: 1) formulation dependent effects, including the impact of the non-ionic detergent used and application of lyophilization to increase the long-term storage stability prior to the point of use (Table 1); 7,26,73 and 2) sequence-dependent effects (Table 2), likely localized within the variable domains given an average similarity of 61 ± 15% compared to >98% across the remaining sequence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Under carefully controlled conditions, and given suitably low residual moisture content (<0.5%), lyophilization is known to be capable of increasing storage stability. 73 Based on the above considerations, the observed thermal stability differences between the native state of bevacizumab and all other samples studied may be represented by one or both of the following sample dependent variables: 1) formulation dependent effects, including the impact of the non-ionic detergent used and application of lyophilization to increase the long-term storage stability prior to the point of use (Table 1); 7,26,73 and 2) sequence-dependent effects (Table 2), likely localized within the variable domains given an average similarity of 61 ± 15% compared to >98% across the remaining sequence.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to Polysorbate 20, Polysorbate 80 was shown to exhibit a higher affinity for the Fab domain, and as a consequence may, provide enhanced levels of protection against tertiary structure perturbations within this region of the mAb. 26,27 Consistent with above concerns regarding long-term thermal stability on biotherapeutic HOS, we investigated the consequences of accelerated storage conditions (6 months at 25 ± 2°C, 60 ± 5% RH (relative humidity)) on four commercially available mAbs, bevacizumab (Avastin), trastuzumab (Herceptin), rituximab (Rituxan), and the NIST reference material 8671 (NISTmAb). 28 To provide additional sample comparison data, two different lots of rituximab were studied, including an in-date (unexpired) lot and an out-of-date (expired) lot with an expiration date several years before the start of the study, which was used as a negative control.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…131 Indeed, polysorbate 80 seems to be one of the most protecting surfactant against mechanical stresseinduced aggregation when compared to some other nonionic and anionic surfactants at the same concentration, 130 and also seems to be less perturbing toward mAb higher structure stability when compared to polysorbate 20. 132 This protection also depends on the protein to surfactant ratio. 29,93,130 In addition, surfactants have been shown to act as chemical chaperones, increasing rates of protein refolding and thus reducing aggregation.…”
Section: Excipientsmentioning
confidence: 99%
“…Overall protection is however still increased. 132 Close to surfactants, cyclodextrins may be an alternative as they could present a good toxicological profile, no peroxide generation and be less disturb toward proteins. 139 In 1992, Ressing et al 140 showed that hydroxypropyl-b-cyclodextrin can protect mAbs from aggregation due to lyophilization.…”
Section: Excipientsmentioning
confidence: 99%